Perancangan Sistem Informasi Antrian pada Puskesmas Munte Berbasis Web - Katarina Eteta br Ginting; Rimbun Siringoringo; Roni Jhonson Simamora; Eva Julia G. Harianja (Majalah Ilmiah METHODA, 2025)
The Community Health Center is a primary healthcare facility that provides medical services to the public. However, at the Munte Community Health Center, the patient queuing process is still carried out manually by recording names in a registration book, which leads to various issues such as long queues, disorderliness, and delays in service delivery. This study aims to design a web-based queue information system to improve service efficiency, facilitate the registration process, and streamline patient calling. The development method used is the waterfall model, which includes the stages of requirement analysis, system design, implementation, and testing. The results of the study produced a queue information system that enables digital patient registration, patient data management, and automatic patient calling based on sequence, with access through a local network and an interface designed to be simple for staff to use. Testing shows that the system functions well, reduces patient waiting time, and improves service flow. Thus, this web-based queue information system is expected to support the provision of more effective, efficient, and comfortable healthcare services at the Munte Community Health Center, as well as promote the realization of digital transformation in healthcare.